1986
DOI: 10.1111/j.1471-4159.1986.tb01755.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of the Glucose Transporter in the Mammalian Brain

Abstract: We used [3H]cytochalasin B as a specific ligand to study the glucose transporter of the following tissue preparations: (a) microvessels derived from the cerebral cortex and cerebellum of the rat and pig, (b) particulate fractions of the cerebral cortex and cerebellum of the rat and pig, (c) lateral, third, and fourth ventricular choroid plexus of the pig, and (d) synaptosomes from the pig cerebral cortex. Specific, D-glucose-displaceable binding of [3H]cytochalasin B was present in all the preparations studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
26
1

Year Published

1986
1986
2007
2007

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 66 publications
(32 citation statements)
references
References 28 publications
5
26
1
Order By: Relevance
“…Our results indicate the presence of a single class of saturable binding sites with a similar dissociation constant for each subcellular fraction. The maximal binding capacity of the P 10000 x g fraction present in chromaffin tissue correlates well with similar fractions from cerebral cortex and cerebellum from pig and rat brain [10,11]. When more enriched fractions from neuroblastoma and astrocytes were compared, the values reported were also very similar to that found in chromaffin tissue membrane preparations (12-16 pmol/mg protein) [25].…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Our results indicate the presence of a single class of saturable binding sites with a similar dissociation constant for each subcellular fraction. The maximal binding capacity of the P 10000 x g fraction present in chromaffin tissue correlates well with similar fractions from cerebral cortex and cerebellum from pig and rat brain [10,11]. When more enriched fractions from neuroblastoma and astrocytes were compared, the values reported were also very similar to that found in chromaffin tissue membrane preparations (12-16 pmol/mg protein) [25].…”
Section: Discussionsupporting
confidence: 64%
“…The glucose transport and transporters in neural tissues have been characterized [10,11], even for chromaffin cells [12], and the stimulatory effects of secretagogues and insulin established [13].…”
Section: Introductionmentioning
confidence: 99%
“…Regional differences in the blood-to brain glucose transport may be due to (a) differ ences in the density and/or affinity of the glucose transporter of regional brain capillaries; (b) differ ences in vascular arrangement and capillary geom etry, which include capillary density and length; or (c) differences in capillary BF characteristics such as capillary hematocrit and flow velocity. The first possibility is not supported by studies of the glu cose transporter of isolated regional brain micro vessels (Dick and Harik, 1986).The object of this study was to ascertain whether regional differences in the blood-to-brain glucose transport are unique to glucose or if they are a function of regional differences in capillary distri bution and perfusion. To achieve our aim, we used two strategies: We studied (a) the regional blood-718 1.…”
mentioning
confidence: 80%
“…Regional differences in the blood-to brain glucose transport may be due to (a) differ ences in the density and/or affinity of the glucose transporter of regional brain capillaries; (b) differ ences in vascular arrangement and capillary geom etry, which include capillary density and length; or (c) differences in capillary BF characteristics such as capillary hematocrit and flow velocity. The first possibility is not supported by studies of the glu cose transporter of isolated regional brain micro vessels (Dick and Harik, 1986).…”
mentioning
confidence: 81%
“…When radiolabeled cytochalasin B, which binds specifically to glucose transporter molecules, was used as a ligand, the existence of variations in the density of labeling of cerebellar microvessels was also reported (Dick and Harik 1986;Tucker and Cunningham 1988). Dick and Harik (1986) observed that the labeling density with cytochalasin B was slightly lower in the rat cerebellar than in cerebral microvessels, whereas in the pig, this lowering was more pronounced (almost to 50%). According to these authors, the differences in density of GLUT-1 molecules in the microvascular wall are related to different utilization of glucose in a given brain region: higher density of transporter molecules means higher glucose utilization by neurons.…”
Section: Figure 15mentioning
confidence: 99%